Pengaruh The Big Five Personality terhadap Suicide Ideation pada Emerging Adulthood - Rahmawati, Febby Ineza; Nurmina, Nurmina (ALSYS, 2024)
This study aimed to investigate the extent to which the Big Five Personality traits influence suicidal ideation in individuals transitioning into emerging adulthood. A quantitative approach was employed, with a purposive sample of 100 individuals aged 18-25 who had experienced suicidal ideation. Two primary instruments were utilized: the IPIP-BFM-50 scale to measure participants' personality traits on the five dimensions, and the Beck Scale for Suicide Ideation to assess the frequency and intensity of suicidal thoughts. Multiple linear regression analysis was conducted to analyze the data. Results indicated that of the five personality dimensions, only Neuroticism demonstrated a significant relationship with suicide ideation. Specifically, higher scores on the Neuroticism dimension were associated with a greater likelihood of experiencing suicidal thoughts.